Facet-resolved electrochemistry of monolayer-modified silicon crystals - Zhang, Song (Curtin University, 2022)
The main aim of this dissertation is the study of electrochemical reactions on readily accessible, but seldom used, highly conductive crystal facets of silicon. The thesis explores semiconductor photo effects at Si(211) and Si(110), links between electrical conductivity and electrochemical rates, and onset of reversible silica/silicon redox chemistry at highly conductive crystal defects. The outcome is to expand silicon electrochemistry beyond conventional Si(100) and Si(111) crystallographic cuts.